2002
DOI: 10.2172/957378
|View full text |Cite
|
Sign up to set email alerts
|

Potential Signatures of Semi-volatile Compounds Associated With Nuclear Processing

Abstract: Semi-volatile chemicals are associated with nuclear processes and can provide sticky residues or signatures that will attach to piping, ducting, soil, water, or other surface media. Volatile compounds that are more suitable for electro-optical sensing have been well studied. However, the semi-volatile compounds have not been well documented or studied. A majority of these semi-volatile chemicals are more robust than typical gaseous or liquid chemicals and can have lifetimes of several weeks, months, or years i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Chemicals with low environmental stability must be detected and measured quickly after release or they may be converted to a chemical by-product that is not useful for the process identification. The Probasco et al (2002) study cited previously also reported results of a similar stability/uniqueness assessment for volatile effluents from nuclear material processing.…”
Section: Chemical Attributes Tablesmentioning
confidence: 70%
“…Chemicals with low environmental stability must be detected and measured quickly after release or they may be converted to a chemical by-product that is not useful for the process identification. The Probasco et al (2002) study cited previously also reported results of a similar stability/uniqueness assessment for volatile effluents from nuclear material processing.…”
Section: Chemical Attributes Tablesmentioning
confidence: 70%
“…In general, organophosphorus compounds have similarly poor volatility to long-chained amines but have lower persistence as they are subject to photo-and bacterial decomposition. A table of these compounds, decomposition products, and calculated vapor pressures was published by Probasco et al (2002).…”
Section: Chemical Detectionmentioning
confidence: 99%
“…Even if effluents are individually nonspecific, such as acidic gases, certain mixtures of effluents may be specific for reprocessing. A catalog of chemical variants has been published (Probasco et al 2002), and a study of source terms is now publicly available (Birnbaum et al 2004). Considerable research will be needed to discern which of the many hundreds of species are reliable and detectable signatures.…”
Section: Reprocessingmentioning
confidence: 99%
“…The high-volume chemicals used in these processes that may provide good probative information can be radiological, volatile, or semi-volatile. A comparison was made on more than 220 chemicals that are used in various processes throughout the nuclear fuel cycle (Probasco et al 2002, Birnbaum et al 2004 ). Semi-volatile chemicals are used in almost all facets of this cycle including raw material acquisition, isotope enrichment, fuel fabrication, reactor operations, actinide separations, and device manufacturing.…”
Section: Chemicals Used In Nuclear Fuel Processingmentioning
confidence: 99%
“…Chemicals in the existing database (Probasco et al 2002, Birnbaum et al 2004 ) were evaluated on the basis of two criteria that are important for determining the promising options for effluent detection.…”
Section: Chemicals Used In Nuclear Fuel Processingmentioning
confidence: 99%